Were galician medieval jews rich? (Estudios de Historia de España, 2017)
In spite of the little amount of Jews in Galicia and the scarce documents that have been kept as a consequence, it can be noticeable that the Jewish population had suffered the same changes and stereotypes than the rest of the Castilian kingdom. Such stereotypes have been present since the 14th century, which almost coincided with the first documents kept about the Jewish presence in Galicia. One of the main accusations was the fact of being owners of huge fortunes when, actually, there is some evidence that show that Galician Jews were mainly humble and poor craftsmen, as it is shown by the council debtors lists
Keywords: Jews – Galicia – Middle Ages – Stereotypes – Social History